Kebijakan Pemerintah Indonesia melalui Sekuritisasi Migrasi Pengungsi Rohingya di Aceh tahun 2012-2015 - Alunaza, Hardi; Juani, M. Kholit (Indonesian Perspective, 2017)
This paper is attempted to describe Indonesian policy in dealing with Rohingya Refugees inAceh in 2015. This paper took the specific interest on securitization of migration theory to analyzethe issue. This paper sketches three important points regarding Indonesian policy to solve the Rohingyarefugees problems in Aceh. First, Indonesian Government will make new policy by adjustingthe existing legislation on refugees. Second, Indonesia will accommodate the displaced Rohingyapeople. Third, Indonesian Government will work together with international community to solvethe problems of Rohingya refugees.Keywords: Indonesian Policy, Rohingya Refugees, Securitization of Migration